2001
DOI: 10.1002/1099-0682(200109)2001:10<2497::aid-ejic2497>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Tris(indenyl)lanthanoid Complexes (Ln = La, Pr, Nd) Containing either (S)-(−)-Nicotine or Two Simpler Pyridine Bases

Abstract: Novel examples of the complex of the type [Ln(Ind)3·Nic] [Ind = indenyl; Nic = (S)‐(−)‐nicotine] with Ln = La (2), Pr (3), and Nd (4) have been synthesised, along with their “parent” system [LaCp3·Nic] (1). Complexes 2−4 were structurally, exhaustively characterised (XRS, 1H NMR spectroscopy). Attempts to prepare homologues of 3 with achiral N‐bases, pyridine, α‐picoline, β‐picoline, 2,6‐dimethylpyridine, 2,6‐bis(tert‐butyl)pyridine, 2,2′‐bipyridine, and 4,4′‐dimethyl‐2,2′‐bipyridine, were successful with only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…But very little structural information on these compounds is available [4][5][6][7][8][9][10][11][12][13][14]. We have previously reported on crystal structure of the Cu(II) and Hg(ü) complexes of the type [Cu4Cu-Br)60(Nicotine) 4 ], [[HgX 2 (Nicotine)]"] (X = Br, I) [10][11][12]. The title compound is a neutral monomelic zinc(II) complex.…”
Section: Discussionmentioning
confidence: 99%
“…But very little structural information on these compounds is available [4][5][6][7][8][9][10][11][12][13][14]. We have previously reported on crystal structure of the Cu(II) and Hg(ü) complexes of the type [Cu4Cu-Br)60(Nicotine) 4 ], [[HgX 2 (Nicotine)]"] (X = Br, I) [10][11][12]. The title compound is a neutral monomelic zinc(II) complex.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the preparation and characterization of nicotine-metal complexes have been reported. But very little structural information on these compounds is available [4][5][6][7][8][9][10][11][12][13][14]. We have previously reported on crystal structure of the Cu(II) and Hg(II) complexes of the type [Cu 4 (m-Br) 6 O(Nicotine) 4 ], [[HgX 2 (Nicotine)] n ](X=Br, I) [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, 2 represents the first tris(fluorenyl) rare-earth-metal complex. In stark contrast, tris(indenyl) derivatives (Ind) 3 Ln and (Ind) 3 Ln(Do) have been extensively investigated (Do = neutral donor molecules), 35 including the crystal structures of Ind 3 Ce(py) 36 and Ind 3 Ce(THF). 13 Moreover, the existence of 2 definitely rules out sterics to be the crucial factor for the formation of 1 Ce,Cl .…”
Section: ■ Introductionmentioning
confidence: 99%